Penerapan Model Pembelajaran Talking Stick Untuk Meningkatan Hasil Belajar IPS Siswa Kelas V SD Negeri Sarongsong - Kirana Mangimbulude; Roos M.S. Tuerah; Hetty J. Tumurang (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to improve social studies learning outcomes through the talking stick learning model in class V of Sarongsong State Elementary School. This research is classroom action research (PTK) which consists of several stages, namely planning, action, observation and reflection. Data about learning activities in class was obtained from teacher observations in managing learning, and tests on student learning outcomes. The data obtained is processed using percentages according to predetermined activity criteria. The results of this research show that the learning outcomes of class V students at Sarongsong State Elementary School on ethnic groups in Indonesia by applying the talking stick learning model in cycle I was 67.25% (which was not completed according to the classical KKM) and increased in cycle II, namely 88 % (completed using the classical KKM) Based on the results of data analysis, it can be concluded that applying the talking stick learning model can improve student learning outcomes in Indonesian language learning in class V of Sarongsong State Elementary School. It can be seen that the increase in learning outcomes in social studies subjects from cycle I to cycle II increased by 18.25%. Based on these conclusions, it is hoped that Sarongsong State Elementary School teachers can apply the talking stick learning model to other subjects in order to improve student learning outcomes.